Impact of mixed ownership reforms on firm innovation: Empirical evidence from China - Kai Wan; Xiaolin Yu (Journal of Applied Economics, 2022)
Based on data from Chinese A-share listed companies from 2008-2018, an investigation is carried out upon the impact of mixed ownership reforms and relative control transfers on corporate innovation before and after the occurrence of mixed ownership reforms, and relative control transfers in state-owned and private enterprises, as well as their mechanisms of action. A double-difference propensity score matching method is adopted. It has been found that mixed ownership reforms are more likely to promote innovation in SOEs, particularly in monopolistic industries. A further sub-sample test reveals that in state-owned enterprises in monopolistic industries, the acquisition of relative control by private shares can amplify the innovation effect of mixed ownership reforms. In private companies in competitive industries, state-owned shares can only fuel innovation if they gain relative control. Reducing agency costs and easing financing constraints are important channels for mixed ownership reform to promote corporate innovation.
Keywords: 330; agency costs; corporate innovation; financing constraints; Mixed ownership reform; relative control transfer